The Status of Idumea in Early Hellenism (Diod. 19. 95. 2; 19. 98. 1) - Starikova, Arina (Hyperboreus, 2022)
Diodorus mentions Idumea twice, but pointing to its different administrative territorial statuses: an eparchy in 19. 95. 2 and a satrapy in 19. 98. 1. The paper shows that Diodorus borrowed the term σατραπεία from his source, perhaps from Posidonius (not Hieronymus of Cardia, as usually supposed), and the second term ἐπαρχία is Diodorus’ own. This conclusion is based on the usage of the term σατραπεία by Posidonius and on the fact that a passage in which Idumea is mentioned is included in the account of the Dead Sea, which probably goes back to Posidonius. Besides, arguments are given for keeping the manuscript reading ἐπαρχία without changing to ὑπαρχία (Diod. 19. 95. 2) and for preserving the expression τὴν σατραπείαν τῆς Ἰδουμαίας (Diod. 19. 98. 1), in which H. Bengtson supposed a gloss. It is possible to preserve the manuscript reading in these two cases, because the words ἐπαρχία and σατραπεία were used not only as an indication of an official administrative unit, but also as a colloquial designation of a certain region. This explains Appian’s testimony about 72 satrapies under Seleucus I, as well as many cases of the use of the word ἐπαρχία in the sense of “region” (not as a term of administrative unit). Such a usage of terms makes it difficult to ascertain the official status of Idumea. It can be clarified by the rare testimonies of other authors (thus, Flavius designates Idumea as a toparchy).